Riches of the forest: food, spices, crafts and resins of Asia [Japanese] - López, C.; Shanley, P. (Center for International Forestry Research, 2008)
This book contains 20 case studies that explain how a selection of forest resources featuring forest plans, animals and fungi are harvested, processed and traded. The botanical cases are presented according to the main part of the plant being used - the fruit, bark or resin. Sometimes the plants have multiple uses, or different cultures may use the same part of a particular plant in different ways. Animals and animal products that require forest habitat are also critical for rural livelihoods, and are represented in this volume by edible bird's nests and insect larvae. In each case, the book describes the main characteristics of the forest product, its historical usage, harvesting and management, and how it is processed and traded. In closing, each author comments briefly on trends and current issues regarding the resource. The final chapter reviews common themes and lessons that can be drawn from these cases.